Lithium Production and Recovery Methods: Overview of Lithium Losses - Vladimír Marcinov; Jakub Klimko; Zita Takáčová; Jana Pirošková; Andrea Miškufová; Marcus Sommerfeld; Christian Dertmann; Bernd Friedrich; Dušan Oráč (Metals, 2023)
The objective of this study is to describe primary lithium production and to summarize the methods for combined mechanical and hydrometallurgical recycling of lithium-ion batteries (LIBs). This study also aims to draw attention to the problem of lithium losses, which occur in individual recycling steps. The first step of hydrometallurgical treatment is leaching, which is an effective method capable of transferring over 99% of the present metals to the leach solutions. Extraction of metals after leaching can be conducted using various methods, with precipitation being the most commonly used. The precipitation of other metals can result in the co-precipitation of lithium, causing total lithium losses up to 30%. To prevent such losses, solvent extraction methods are used to selectively remove elements, such as Co, Ni, Al, and Mn. Solvent extraction (SX) is highly effective, reducing the losses to 3% per extraction stage and reducing overall lithium losses to 15%. After the refining, lithium is precipitated as lithium carbonate. High lithium carbonate solubility (1.5 g/L) and high liquid to solid leaching ratios require costly and avoidable operations to be implemented in order to enhance lithium concentration. Therefore, it is suggested that more studies should focus on multistage leaching with lower L/S ratios.